2022
DOI: 10.1111/imig.13018
|View full text |Cite
|
Sign up to set email alerts
|

Measuring residential segregation in multi‐ethnic and unequal European cities

Abstract: Immigration flows and social inequalities reflect increased social and multi-ethnic segregation in contemporary urban Europe. For a better understanding of these processes, the present study investigates the main strengths of the multigroup residential indices, testing sensitivity and reliability under different metropolitan contexts in five European countries. These indices focus on different research dimensions and approach multi-group residential segregation conceptually and mathematically in a different wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 127 publications
1
7
0
Order By: Relevance
“…These outcomes support the 'twin deficit hypothesis' (Miller and Russek 1989;Cavallo 2005;Corsetti and Müller 2006;Kim and Roubini 2008;Algieri 2013;Badinger et al 2017;Afonso et al 2022). Relating budget deficits to trade deficits, these outcomes had important policy implications for economic competitiveness (e.g., Rontos et al 2016;Di Feliciantonio et al 2018;Benassi et al 2022). Moreover, we explicitly examined the effects of unemployment on the evolution of public budget deficits, regarded as a significant policy issue (Salvati and Benassi 2021).…”
Section: Logical Framework and Scope Of The Studysupporting
confidence: 52%
“…These outcomes support the 'twin deficit hypothesis' (Miller and Russek 1989;Cavallo 2005;Corsetti and Müller 2006;Kim and Roubini 2008;Algieri 2013;Badinger et al 2017;Afonso et al 2022). Relating budget deficits to trade deficits, these outcomes had important policy implications for economic competitiveness (e.g., Rontos et al 2016;Di Feliciantonio et al 2018;Benassi et al 2022). Moreover, we explicitly examined the effects of unemployment on the evolution of public budget deficits, regarded as a significant policy issue (Salvati and Benassi 2021).…”
Section: Logical Framework and Scope Of The Studysupporting
confidence: 52%
“…This work makes several contributions to the existing literature. First, it advances the analysis of Sri Lankans' allocation model in Italy with respect to a previous study conducted by the authors (Benassi et al, 2023b). In particular, the present study extends the context of analysis from solely the main southern Italian municipalities analysed in the previous work, to a set of municipalities covering the entire geographical territory of Italy.…”
Section: Introductionmentioning
confidence: 58%
“…Recent studies have contributed to the body of knowledge on residential segregation in Europe. They have found that urban segregation in the South of Europe has increased in recent years, narrowing the gap with the North, where higher levels of inequality and segregation have traditionally been observed (Arapoglou, 2012;Benassi et al, 2020aBenassi et al, , 2023bPanori et al, 2019). Other studies have focussed on specific territorial partitions, such as the analysis of Southern Europe by Arbaci (2008) and the comparison of different main Spanish and Italian cities by Benassi et al (2020b), as well as the studies conducted by Ciommi et al (2022), Di Feliciantonio and Salvati (2015), Rontos et al (2016), Salvati et al (2016) and Zambon et al (2017) examining residential segregation in urban European contexts.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, official statistics from (continuous) administrative data sources and socioeconomic sampling surveys were affected by two types of interacting errors (namely, the systematic component [basically associated with recording mistakes] and the random component, associated with sampling errors, poor comparability of recording systems and registration rules over long times, and technological change). Based on these considerations, population census data were considered an appropriate source of information for studies addressing long-term metropolitan growth (Siedentop and Fina, 2012; Zambon et al, 2018; Benassi et al, 2022).…”
Section: Methodsmentioning
confidence: 99%